2017
DOI: 10.17795/semj41483
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Socioeconomic Factors and Food Security in Pregnant Women

Abstract: Background: Food security is among the phenomena that have influenced the worldwide policy-making in the recent years. Furthermore, recent studies have reported extensive food insecurity in Iran. Objectives: The present study aimed at defining the levels of food security and investigating its correlation with socioeconomic factors among pregnant women in city of Rasht (Iran) in 2014. Methods: The present cross sectional study included 420 pregnant women in their 14 to 42 weeks of pregnancy. The sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
3
12
1
1
Order By: Relevance
“…To the best of our knowledge, no studies have been conducted evaluating the association of food insecurity with preterm labor. The results of other studies pinpointed the association of food insecurity with maternal adverse outcomes such as gestational diabetes, excessive overweight during pregnancy, and hypertension (11, 23).…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, no studies have been conducted evaluating the association of food insecurity with preterm labor. The results of other studies pinpointed the association of food insecurity with maternal adverse outcomes such as gestational diabetes, excessive overweight during pregnancy, and hypertension (11, 23).…”
Section: Discussionmentioning
confidence: 98%
“…A few studies have measured the status of food insecurity among pregnant women. Yadegari et al (2014) reported a prevalence of 30.9% in Rasht province (6). Moreover, Laraia et al (2006) reported a marginal prevalence of 15% (7).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for evaluating the relationship between SDH and food insecurity was 329 with respect to a prevalence rate of 31% (P, 31%; d, 0.05) (6). In addition, with regard to the sampling method (cluster sampling) and design effect of 2, the sample size was measured at 658.…”
Section: Study Design and Sampling Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Women with poor economic status may face restrictions that may affect their pregnancy. In the study of Yadegari et al (2017), 30.9% of pregnant women did not have food security; they stated that food security is related to socioeconomic factors of the family, monthly income and monthly cost of food supply [ 15 ]. Working women who participated in this study stated that they did not have enough time for cooking and preparing proper nutrition for themselves during pregnancy and therefore felt deficient in themselves; In this regard, Jong (2017) and colleagues in their study found that energy, protein, vitamin B2, vitamin C, calcium and potassium levels were significantly lower in working pregnant women [ 16 ].…”
Section: Discussionmentioning
confidence: 99%